2011
DOI: 10.5489/cuaj.11110
|View full text |Cite
|
Sign up to set email alerts
|

Childhood sexual trauma in women with interstitial cystitis/bladder pain syndrome; a case control study

Abstract: Childhood traumatic events, in particular sexual abuse and extreme illness, are reported as more common in IC/BPS patients than controls. Early trauma, such as the occurrence of sexual abuse, is associated with some differences in patient adjustment (e.g., pain, quality of life, depression) but this impact appears to be, at most, very modest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Prior individual studies of women with IC/BPS have indicated increased levels of anxiety and depression, catastrophizing, and childhood trauma compared to healthy controls [6, 7] [8, 15, 16]. It has been hypothesized that men with CP/CPPS may have similar difficulties but the case-control literature is very small [9] [10].…”
Section: Discussionmentioning
confidence: 99%
“…Prior individual studies of women with IC/BPS have indicated increased levels of anxiety and depression, catastrophizing, and childhood trauma compared to healthy controls [6, 7] [8, 15, 16]. It has been hypothesized that men with CP/CPPS may have similar difficulties but the case-control literature is very small [9] [10].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, although stress definitely plays a role in exacerbating the symptoms, its role as a causative factor is much less clear. 23, 24 In both humans and domestic cats, the number of co-morbidities that accompany IC seems to be a feature of a more system-wide disorder. Moreover, effective multimodal environmental modification for cats with FIC has been found to mitigate signs of comorbid disorders in both clinical and laboratory studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies measured stress and coping by assessing catastrophic thought processes, 18,19,23-26 perceived stress, 9,23,24 and self-efficacy. 27,28 Catastrophizing, or an internal exaggeration of events, rumination, or sense of helplessness in response to pain, is consistently related to worsened outcomes in mental and physical functioning.…”
Section: Stress and Copingmentioning
confidence: 99%
“…Six studies measured abuse prevalence via validated selfreport, 5,9,24,29 non-validated questionnaires, 30,31 and clinical interview of trauma exposure. 30 One study measured dissociative tendencies.…”
Section: Trauma Sequelaementioning
confidence: 99%
See 1 more Smart Citation